Complications following ankle arthroscopy: a systematic review. (1st March 2023) - Arshad, Zaki; Aslam, Aiman; Al-shdefat, Sofyan; Khan, Rahul; Jamil, Omar; Bhatia, Maneesh
Abstract : Aims: This systematic review aimed to summarize the full range of complications reported following ankle arthroscopy and the frequency at which they occur. Methods: A computer-based search was performed in PubMed, Embase, Emcare, and ISI Web of Science. Two-stage title/abstract and full-text screening was performed independently by two reviewers. English-language original research studies reporting perioperative complications in a cohort of at least ten patients undergoing ankle arthroscopy were included. Complications were pooled across included studies in order to derive an overall complication rate. Quality assessment was performed using the Oxford Centre for Evidence-Based Medicine levels of evidence classification. Results: A total of 150 studies describing 7, 942 cases of ankle arthroscopy in 7, 777 patients were included. The overall pooled complication rate was 325/7, 942 (4.09%). The most common complication was neurological injury, accounting for 180/325 (55.4%) of all complications. Of these, 59 (32.7%) affected the superficial peroneal nerve. Overall, 36/180 (20%) of all nerve injuries were permanent. The overall complication rate following anterior ankle arthroscopy was 205/4, 709 (4.35%) compared to a rate of 35/528 (6.6%) following posterior arthroscopy. Neurological injury occurred in 52/1, 998 (2.6%) of anterior cases using distraction, compared to 59/2, 711 (2.2%) in cases with no distraction. The overall rate of major complications was 16/7, 942 (0.2%), with the most common major complication – deep vein thrombosis – occurring in five cases. Conclusion: This comprehensive systematic review demonstrates that ankle arthroscopy is a safe procedure with a low overall complication rate. The majority of complications are minor, with potentially life-threatening complications reported in only 0.2% of patients. Cite this article: Bone Joint J  2023;105-B(3):239–246.